ISOLASI SENYAWA ANTIBAKTERI DAUN JAMBU BIOA (Eugenia densiflora Bl.) DAN PENENTUAN KONSENTRASI HAMBAT MINIMUM (KHM) TERHADAP BAKTERI Escherichia coli - Syarifah, Syarifah (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2013)
The research about Isolation Antibacterial Agent of jambu Bioaâs leaves and Determinated the Minimum Inhibitory Concentartion (MIC) for Escherichia coli was conducted from September â December 2005. The isolation antibacterial agent was done at Laboratory of Genetic and Biotechnology, Biology Departemen, Faculty of Mathematic and Natural Science, University of Sriwijaya. The aims of this study were to asses antibacterial agent of Jambu bioaâs to determine the active chemical compound. The process isolation of antibacterial compounds was done in three ways : extraction by using soxhlet, fractionation by using liquid vacuum chromatographic. Antibacterial activity tested by using the agar diffusion method. The test organism were Escherichia coli. The result proved that n â hexane and aethylacetate have been examinated test bacterium Escherichia coli. Bioactive compound fraction N4, N5, N6 from n- hexane and E3, E4, E5 from aethylacetate. The active compound isolate N1 with Rf 0,22, isolate N2 with Rf 0,87 are fenolÂ  and isolate E1 with Rf 0,6 is terpenoid.Key words : MIC, fractionation, fenol, tetracycline